The History of Female Sufi Figures as Role Models of Good Behavior (Akhlakul Karimah) - Tukiran, Tukiran (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article seeks to explore the severe history of Sufi figures from the female group with the aim of knowledge and wisdom of akhlakul karimah examples for readers, especially female students. This research is a descriptive qualitative type because the data studied is not numerical data, this research uses the Grounded Theory strategy, which is to explore a topic to be studied in depth with disciplinary theory, the technique used is Library Research, which is a study based on non-field literature data, with content analysis technique, which is a process of rigorous and systematic procedures for analyzing, testing, and clarifying data. The result of this study is that women and men have equality in their efforts to approach and achieve the Perfect (spirituality) in addition to equality in social roles. In Sufism for example, Robi'ah al-Adawiyah can surpass the level of men. This shows that men and women have the same opportunity and position to reach a certain level of piety. It all depends on their abilities and endeavors. In any case, women's involvement in Islamic mysticism has contributed immensely to the development of Islam and become a force in itself for Islam.